A comparative study of several constitutive models for powder metallurgy tungsten at elevated temperature. (15th January 2016) - Wang, Jin; Zhao, Guoqun; Chen, Liang; Li, Jinlu
Abstract: The isothermal hot compression tests for powder metallurgy pure tungsten were carried out by using Gleeble 3800 thermo mechanical simulator at deformation temperatures from 1523 K to 1823 K and strain rates from 0.001 s − 1 to 1 s − 1 . The deformation behavior of powder metallurgy pure tungsten at elevated temperature were studied, and six constitutive equations were respectively established based on Arrhenius model, Johnson–Cook model, modified Johnson–Cook model, Zerilli–Armstrong model, modified Zerilli–Armstrong model, and KHL model. Moreover, the predictability of the derived constitutive equations was evaluated by using the correlation coefficient ( R c ) and average absolute relative error (AARE). The results show that flow stress of pure tungsten is affected not only by strain rate and deformation temperature, but also by strain. The flow stress of pure tungsten at elevated temperature could be well described by Arrhenius model, modified JC model, modified Zerilli–Armstrong model, and KHL model. The present study can provide some important and basic data for the simulation of plastic deformation processes of powder metallurgy pure tungsten. Graphical abstract: Highlights: Hot compression tests on pure tungsten at elevated temperatures were finished. Six constitutive equations were established for pure tungsten. Predictability of the constitutive model is evaluated in terms of the coefficient and average absolute relative error.